Feasibility study of a ZnWO4 scintillator for exploiting materials signature in cryogenic WIMP dark matter searches - Kraus, H; Mikhailik, V; Ramachers, Y; Day, D; Hutton, K; Telfer, J (2005)
The mass number dependence of the WIMP-nucleus scattering offers a method for identifying a true WIMP signal over a neutron background. In this Letter we present a study on using a combination of ZnWO4 and CaWO4 absorbers to exploit this materials signature for WIMP detection. Using monochromatic X-ray radiation we examined the temperature variation of the luminescence properties for both materials and showed that at low temperature (8 K) ZnWO4 exhibits ∼10% higher light yield than CaWO4. Analysis of relevant optical properties indicates that ZnWO4 is a suitable cryogenic scintillator. We show that already modest exposure in the region of ∼5 kg yr should allow the detection of WIMP interaction for cross sections at the level of current experimental sensitivities. The combination of these two tungstates could form the basis of the first multi-target detector capable of WIMP identification through materials signature. © 2005 Elsevier B.V. All rights reserved.